The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph191912490
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Predictors of Financial Stress and Financial Well-Being among the Bottom 40 Percent (B40) Households in Malaysia

Abstract: This paper aims to analyse factors affecting financial stress among the Bottom 40 Percent (B40) group of Malaysian households, reflecting overall financial well-being. Data were collected through questionnaires from 1008 respondents across five major regions in Malaysia. The data were analysed using Exploratory Factor Analysis (EFA) and Partial Least Squares-Structural Equation Modelling (PLS-SEM). This study provides evidence that financial behaviour, financial vulnerability (debt and income), and locus of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…The theory explains how families manage their finances which involves financial behavior (as input), financial resources, and financial knowledge toward achieving their goals or well-being. In addition, Sabri et al (2022) found that financial behavior mediates the influence of financial knowledge and internal locus of control on perceived financial well-being among lowincome young adults in Malaysia. Thus, we posit related hypotheses as follows:…”
Section: Literature Review and Hypothesesmentioning
confidence: 96%
See 1 more Smart Citation
“…The theory explains how families manage their finances which involves financial behavior (as input), financial resources, and financial knowledge toward achieving their goals or well-being. In addition, Sabri et al (2022) found that financial behavior mediates the influence of financial knowledge and internal locus of control on perceived financial well-being among lowincome young adults in Malaysia. Thus, we posit related hypotheses as follows:…”
Section: Literature Review and Hypothesesmentioning
confidence: 96%
“…Thus, based on these arguments, this study postulated that: due to low savings may need more funds in the event of an income shock. Mansor et al (2022) have presented evidence that financial stress impacts the financial well-being of the Bottom 40 Percent (B40) group, where the results show a significantly positive relationship between financial stress and financial vulnerability. Furthermore, unplanned spending behavior may result in an inability to meet basic needs and debt payments as scheduled, which are related to financial vulnerability.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…As previously mentioned, there were abundant numbers of research looking at FWB and the financial behaviours of young people or emerging adults. [ 18 , 62 ], for instance used university or college students as their sample, while other studies surveyed working young adults between a particular age scope [ 8 , 63 ]. Extant studies have their spotlight on youths and young adults since this population group has an significant responsibility, as the potential ‘captain’ who will steer the world into even more difficult circumstances, they deserve special attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several works related to household income and expenditure, nancial literacy, and spending behavior, speci cally in Malaysia, have employed statistical and mathematical modeling methods. Previous studies employed multiple regression methods to identify factors in uencing household spending on sustainable consumption [3], OLS and Tobit estimation methods to determine the effects of these factors on B40 household consumption pattern [4], Exploratory Factor Analysis (EFA) and Partial Least Squares-Structural Equation Modelling (PLS-SEM) to analyze factors affecting nancial stress among the Bottom 40 Percent (B40) group of Malaysian households [5] and investigate the relationship between nancial literacy, nancial behavior, nancial stress, and nancial well-being of B40 group in Malaysia [6]. Their ndings suggested that the government as policymakers and stakeholders focus on factors that could sustain B40 households' consumption level, be aware that the in uence of socioeconomic and demographic factors that play a signi cant role in B40 household consumption; identify the vulnerable groups of households in order to gauge their diminishing ability to sustain spending; and invent more effective and substantial stimulus packages or other measures to reduce the nancial burden on B40 households Machine Learning (ML) on socio-economic data that used Malaysia household income and expenditure data with various results can be seen in [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%